2015
DOI: 10.1140/epjc/s10052-015-3700-6
|View full text |Cite
|
Sign up to set email alerts
|

Higher-order QCD predictions for dark matter production at the LHC in simplified models with s-channel mediators

Abstract: Weakly interacting dark matter particles can be pair-produced at colliders and detected through signatures featuring missing energy in association with either QCD/EW radiation or heavy quarks. In order to constrain the mass and the couplings to standard model particles, accurate and precise predictions for production cross sections and distributions are of prime importance. In this work, we consider various simplified models with s-channel mediators. We implement such models in the FeynRules/MadGraph5_aMC@NLO … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
108
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 101 publications
(108 citation statements)
references
References 113 publications
(177 reference statements)
0
108
0
Order By: Relevance
“…The event rate is normalised to the pp → Y 2 j NLO cross sections shown in Fig. 3. (Note, however, that NLO corrections may also affect the shapes of the kinematic distributions, as shown for the spin-1 and spin-0 cases in [17]; a detailed study of this aspect will be reported elsewhere. )…”
Section: Searches With Missing Energymentioning
confidence: 96%
See 1 more Smart Citation
“…The event rate is normalised to the pp → Y 2 j NLO cross sections shown in Fig. 3. (Note, however, that NLO corrections may also affect the shapes of the kinematic distributions, as shown for the spin-1 and spin-0 cases in [17]; a detailed study of this aspect will be reported elsewhere. )…”
Section: Searches With Missing Energymentioning
confidence: 96%
“…This work follows the DMsimp framework [16][17][18], which provides the DM model files for event generators such as MadGraph5_aMC@NLO [19] as well as for DM tools such as micrOMEGAs [20][21][22] and MadDM [23,24]. The same framework was used previously to study the cases of s-channel spin-1 and spin-0 mediators.…”
Section: Introductionmentioning
confidence: 99%
“…This idea is at the base of the so-called "Simplified Models" [140][141][142][143][144][145][146][147][148][149][150][151][152][153][154] which are customarily adopted especially in the context of collider studies, see e.g., Refs. [130,[155][156][157][158][159][160][161][162][163][164][165][166].…”
Section: Model Setup: Dark Portalsmentioning
confidence: 99%
“…Therefore, in the recent literature simplified models are gaining in importance [12,[70][71][72][73][74][75][76][77]. The usefulness of EFTs and simplified models is illustrated by studies of higher order QCD corrections to DM production at the LHC [78][79][80][81]. These studies show that higher order effects can be very important, but computing them for every single UVcomplete model is clearly impractical.…”
Section: Jhep12(2015)120mentioning
confidence: 99%